Biofortified wheat: Harnessing genetic diversity for improved nutritional quality to eradicate hidden hunger - Kaur, Kuldeep; Sharma, Achla; Mavi, Gurvinder Singh; Srivastava, Puja; Kaur, Harinderjeet; Sharma, Himanshu; Singh, Satinder; Kushwah, Ashutosh; Sohu, Virinder Singh (Wiley, 2022)
The present study is based on backcross introgression lines carrying high grain zinc (Zn) quantitative trait loci (QTL) introgressed from domestic einkorn wheat (Triticum monococcum L.) and wild einkorn wheat (T. boeoticum) in the background of high‐yielding wheat (T. aestivum L.) cultivars of India. Initially, individual trials each for BC1F3 and BC2F3 progenies from different cross combinations were evaluated for grain Zn concentration, yellow pigment content (YPC) and agronomic traits. Highly promising BC1F3 and BC2F3 progenies were identified and advanced in off‐season as ear to progeny rows. A total of 42 BC1F5 and 43 BC2F5 derivatives were evaluated in a single trial where the BC1F5 progenies from recipient parent WH1105 and tetraploid parent Donor 2 were recorded with highest grain Zn (64.1–67.9 ppm) showing up to 35.8% enhancement over recipient. The highest grain YPC (5.35 ppm) was observed for BC1F5 progenies from the cross involving PBW703 (3.34 ppm) as recipient and Donor 7 (6.32 ppm) as tetraploid donor parent. Monitoring of backcross derivatives with the marker YP7A‐2 linked to yellow pigment gene Psy‐A1, also revealed nine lines positive for high yellow pigment allele (Psy‐A1c) indicating introgression from durum wheat (T. durum Desf.). Nineteen high Zn derivatives were shortlisted and selfed for 2 yr (2017–2018 and 2018–2019) to get desirable homozygosity and preliminary yield evaluation was conducted for two consecutive years (2019–2020 and 2020–2021). Introgression lines in the background of PBW698 (IL8 and IL17) were recorded with the highest Zn concentration (51.37 and 51.30 ppm) indicating 55.90% increment over recipient parent with good agronomic performance. These biofortified introgression wheat lines can contribute to mitigating the malnutrition among the masses in developing countries.